2010
DOI: 10.1111/j.1365-2354.2010.01233.x
|View full text |Cite
|
Sign up to set email alerts
|

Disclosing information about randomised controlled trials in oncology: training concept and evaluation of an individualised communication skills training for physicians COM-ON-rct

Abstract: When physicians disclose information about randomised controlled trials, they have to balance the requirements of conducting high standard research and the respect for patients' rights. Physicians need training in this difficult matter. An individualised communication skills training (CST) about randomised controlled trials for oncologists has been developed. The aim of this publication is to describe the concept of our CST and present data of evaluation by the participants: First, a theoretical introduction a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 25 publications
0
31
0
Order By: Relevance
“…Different sources were used to create the half-standardised interview guideline (see box 1) such as literature about manual construction,14 quality of IC,9 15 16 and included aspects from a current communication workshop about clinical trials from the authors 16. The interview covered different aspects of the IC and started with open questions so that patients had the opportunity to give free answers.…”
Section: Methodsmentioning
confidence: 99%
“…Different sources were used to create the half-standardised interview guideline (see box 1) such as literature about manual construction,14 quality of IC,9 15 16 and included aspects from a current communication workshop about clinical trials from the authors 16. The interview covered different aspects of the IC and started with open questions so that patients had the opportunity to give free answers.…”
Section: Methodsmentioning
confidence: 99%
“…Authors reported assessing participants' performance on how to offer the opportunity to participate in clinical trials (with the exception of [40], which does not explicitly mention it). Only six studies instructed participants how to address possible benefits and side effects associated with clinical trials participation [11,29,35,37,45,46]. Generally, authors did not recommend different communication strategies for different phases of clinical trials.…”
Section: Information Conveyedmentioning
confidence: 99%
“…Six studies [10,13,29,38,42,46], reported training participants on the importance of assessing the eligibility of patients for the clinical trials. Authors reported assessing participants' performance on how to offer the opportunity to participate in clinical trials (with the exception of [40], which does not explicitly mention it).…”
Section: Information Conveyedmentioning
confidence: 99%
See 2 more Smart Citations